The alliance : managing talent in the networked age - Hoffman, Reid. (Harvard Business Review Press, 2014)
"For most of the 20th century, the relationship between employers and employees in the developed world was all about stability and lifetime loyalty. That has recently changed, giving way to a transactional, laissez-faire approach that serves neither party well. A new arrangement is needed, the authors argue--one built on alliance (usually temporary) and reciprocity. The high-tech start-up community of Silicon Valley is pointing the way--and companies that wish to be similarly agile and entrepreneurial [may] learn valuable lessons from its example. Under the new compact, both employer and employee seek to add value to each other"--